ANALYSIS CORRELATION BETWEEN SELF-EFFICACY AND COMPETENCE OF BIOLOGY IN SENIOR HIGH SCHOOL - Miftahul Hayati; Yosi Laila Rahmi; Diana Vivanti Sigit (Universitas Negeri Padang, 2021)
The problem that is often faced in the learning process is the low learning competence obtained by students. One of the factors that influence students' learning competence is self-efficacy. The purpose of this study was to determine the relationship between self-efficacy and Biology learning competence of students in class XI MIPA SMAN 1 Hiliran Gumanti. The method used is descriptive correlation using the Spearman rank formula. The results showed that there was a correlation between self-efficacy and Biology learning competence of students with a value of r=0.477 and tcount which was 3.4321 which was greater than t table, which was 2.0218. So, it can be concluded that there is a significant and positive relationship between self-efficacy and Biology learning competence of students in class XI MIPA SMAN 1 Hiliran Gumanti.